2012
DOI: 10.1093/toxsci/kfs220
|View full text |Cite
|
Sign up to set email alerts
|

Assessing a Theoretical Risk of Dolutegravir-Induced Developmental Immunotoxicity in Juvenile Rats

Abstract: HIV-1 integrase inhibitors (INIs) are a promising class of antiretrovirals for the treatment of HIV in adults; there is interest in expanding their use into pediatric populations. A theoretical concern for developmental immunotoxicity was raised after a publication suggested that two HIV INI tool compounds inhibited in vitro cleavage activity of recombination activating genes 1 and 2 (RAG1/2) through the inhibition of their binding to recombination signal sequences. RAG1/2 are required for the development of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…The NOAEL of compound 1 was determined to be greater than 500 mg/kg/day, which provides a significant exposure margin in antiviral therapeutic applications. Dolutegravir had an NOAEL in adult rats of 50 mg/kg/day (Rhodes et al, 2012) and raltegravir showed an NOAEL of 120mg/kg/day (Merck, 2007), although the dosage and study durations were somewhat different from our studies. The maximum tolerated dose (MTD) for compound 1 is also considered to be greater than 500 mg/kg/day.…”
contrasting
confidence: 78%
“…The NOAEL of compound 1 was determined to be greater than 500 mg/kg/day, which provides a significant exposure margin in antiviral therapeutic applications. Dolutegravir had an NOAEL in adult rats of 50 mg/kg/day (Rhodes et al, 2012) and raltegravir showed an NOAEL of 120mg/kg/day (Merck, 2007), although the dosage and study durations were somewhat different from our studies. The maximum tolerated dose (MTD) for compound 1 is also considered to be greater than 500 mg/kg/day.…”
contrasting
confidence: 78%
“…Histone methylation plays a key role in and as such regulates transcription, replication, cell differentiation, genome stability, and apoptosis [62][63][64][65][66]. Mounting evidence points to a role for histone lysine methylation in DSB repair [67][68][69][70][71][72].…”
Section: Histone H3 Dimethylation Of Lys36 At Dsb Sitesmentioning
confidence: 99%
“…The WHO consolidated guidelines on ARV use recommended Efavirenz (EFV 600 mg) based regimen as a preferred first-line choice for HIV-1 treatment based on efficacy and safety data at that time [11]. At the moment, however, INSTI-based HAART regimens are the most preferred for antiretroviral therapy [11,12,13] because of their potency, safety profile, and rare drug-drug interactions [13,14,15]. Dolutegravir (DTG), a new generation INSTI, acts by inhibiting the incorporation of HIV DNA into the T-lymphocyte genome of the host, thereby limiting viral propagation [13].…”
Section: Introductionmentioning
confidence: 99%